REINTERPRETASI TEKS TENTANG WALI DAN SAKSI: Upaya Mewujudkan Kesetaraan Jender dalam Memahami al-Quran dan Hadis - Hamka Hasan (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2016)
Discourse on trustee and witness in marriage is one of the seemingly never-ending controversies. Discussions surrounding it, nevertheless, is regarded as the access point to the equality between the role of men and that of women. Even though both sides whose opinion is contradictory all the way around have the same goal in elevating women’s value and dignity, methods and approaches they conduct in comprehending the religious texts are different to each other. For this reason, the re-interpretation of the texts can presumably bridge the gap. The discourse, however complex it is, can be solved in different situation by using methods developed by traditional and contemporary scholars. This article elaborate principle methods in re-interpreting authoritative religious texts relating to, more particularly, trustee and witness in marriage based on Islamic Jurisprudence, as well as arguments proposed by both sides and the re-interpretation to their arguments.